Philosophical & anthropological reflections on “Caritas in Veritate” encyclical letter by Benedict XVI - Reluz Barturén, Francisco (2010)
Taking as a starting point the analytical reading of “Caritas in Veritate”, the author reflects on how the meaning of the terms – such as love, truth, logos, and others – contained in the encyclical letter applies to human life with in a philosophical and anthropological context. Also, reference is made to the continuity of the Magisterium of the Church and the requirement of the personal commitment of the believer, moreover from the university lecture standpoint.